ETIKA BISNIS ISLAM PADA PERILAKU PEMASARAN DAN KEPUASAN KONSUMEN - Wida Ramdania (Asy-Syari'ah, 2020)
Marketing ethics are an integral part of the Islamic economic system which deals with values that can influence consumer behavior. This study aims to discuss the relationship between ethical concepts of marketing behavior and consumer satisfaction from an Islamic economic perspective. To reconstruct the substantive relationship between ethical concepts of marketing behavior and consumer satisfaction, the literature review analysis method is used in examining secondary sources such as the Qur'anic Tafsir, hadith, journal articles, books, and several other relevant sources. The study results found that ethical marketing behavior in Islam is believed to be conceptually related to customer satisfaction so that it can affect business development. Ethics of marketing behavior and consumer satisfaction must be considered so that the company can face competition, maintains the existence and continuity of its business so that it can provide added value and the highest satisfaction for the company, consumers, and all elements of stakeholders.